PLASMACYTOMA OF THE THYROID GLAND - Gilani, Jawad A; Iqbal, Shaheen; Nasreen, Shagufta; Shahid, Safoora (Journal of Ayub Medical College Abbottabad, 2011)
Among the clinical presentation of plasma cell proliferative disorders the extramedullary plasmacytomas are the most infrequent after multiple myeloma and plasma cell tumours of the bones. The plasmacytoma of the thyroid gland to our knowledge has never been reported from Pakistan so far. We present the clinical picture and clinical challenges posed in diagnosis and treatment by this unusual proliferative disorder. Keywords: Plasmacytoma; Thyroid gland.